2014
DOI: 10.1007/s10459-014-9575-8
|View full text |Cite
|
Sign up to set email alerts
|

Relations between policy for medical teaching and basic need satisfaction in teaching

Abstract: Policy initiatives that aim to elevate the position of medical teaching to that of medical research could influence the satisfaction of three basic psychological needs related to motivation for medical teaching. To explore relations between the satisfaction of three basic psychological needs towards medical teaching and two policy initiatives for medical teaching: (Junior) Principal Lecturer positions [(J)PL positions] and Subsidized Innovation and Research Projects in Medical Education (SIRPMEs). An online qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…Initiatives have recently been taken in this direction, like the introduction of a teaching portfolio for tenure and promotion, teaching fellowships (Engbers et al 2015; Lown et al 2009; Steinert et al 2010), grants for educational innovation, and educational research (Adler et al 2015). It would be interesting to investigate whether these initiatives change the collective stories about teaching and thus make better and more suitable identity narratives available.…”
Section: Discussionmentioning
confidence: 99%
“…Initiatives have recently been taken in this direction, like the introduction of a teaching portfolio for tenure and promotion, teaching fellowships (Engbers et al 2015; Lown et al 2009; Steinert et al 2010), grants for educational innovation, and educational research (Adler et al 2015). It would be interesting to investigate whether these initiatives change the collective stories about teaching and thus make better and more suitable identity narratives available.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, our model does not show the possible effects of obtaining a TQ, (J)PL status, or a SIRPME because we only asked our interviewees about the factors that promoted or inhibited individual teachers in a university hospital in making use of teaching policy incentives. It is conceivable that the actual use faculty make of teaching policy incentives affects individual teachers’ strategy and their motivation for medical teaching, as some studies have shown relations between policy initiatives and individual teachers’ motivation for medical teaching (as an outcome measure for the quality of medical teaching) (Engbers et al 2014 , 2015 ), and other outcomes such as educational leadership (Newman et al 2015 ). Further research, therefore, could usefully explore the effects of the use faculty make of teaching policy incentives.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The literature describes different policy initiatives aimed at developing careers in academic medical teaching (AMEE; AERA; Engbers et al 2013 , 2014 , 2015 ; Jaarsma 2012 ; RCPSC; Schofield et al 2010 ; Sorinola et al 2013 ; Steinert et al 2012 ). Successful implementation depends on faculty making use of these teaching policy incentives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experience in the position [8,18]. The longer a worker performs certain functions, with the more confidence he or she can be called a professional.…”
Section: Non-financial Incentivesmentioning
confidence: 99%